2011
DOI: 10.2223/jped.2105
|View full text |Cite
|
Sign up to set email alerts
|

Mood disorders in children and adolescents: update for pediatricians

Abstract: Objectives: To review epidemiological and etiologic aspects of diagnosis and treatment of mood disorders (MDs) in children and adolescents, with a focus on essential information for pediatricians. Sources:A literature search on MEDLINE, a review of the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders, fourth edition (text revision) (DSM-IV-TR), and a critical analysis of current diagnostic criteria and scientific evidence regarding the etiology of mood disorders were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 76 publications
0
4
0
6
Order By: Relevance
“…Cabe salientar que o humor pode sofrer variações negativas em virtude de situações cotidianas, tais como: discussões com amigos, baixo rendimento escolar, comentários depreciativos de amigos a respeito do peso corporal, brigas familiares, entre outras 12 . Logo, em decorrência das situações estressoras mencionadas, as adolescentes podem aumentar a suscetibilidade para o desencadeamento de comportamentos alimentares de risco para os TA.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Cabe salientar que o humor pode sofrer variações negativas em virtude de situações cotidianas, tais como: discussões com amigos, baixo rendimento escolar, comentários depreciativos de amigos a respeito do peso corporal, brigas familiares, entre outras 12 . Logo, em decorrência das situações estressoras mencionadas, as adolescentes podem aumentar a suscetibilidade para o desencadeamento de comportamentos alimentares de risco para os TA.…”
Section: Resultsunclassified
“…Segundo Farias e Cordeiro 12 , o estado de humor no sexo feminino pode ser afetado negativamente em função das mensagens subliminares midiáticas que exaltam ideais estéticos, do baixo rendimento escolar e das discussões fervorosas com familiares ou amigas. Considerando a possível relação entre o estado de humor e os comportamentos alimentares de risco para os TA 3,[13][14][15][16] , as situações estressoras mencionadas acima podem predispor as adolescentes à adoção de comportamentos alimentares de risco para os TA.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…This result was surprising, because as previously described, sleep is related to psychological morbidity in adolescents and mood disorders. 21 Studies have found a bidirectional relationship between psychological morbidity, mental health, and sleep quality. 22,23 Another study comparing depressed adolescents with control groups, using EEG, reported inconsistent conclusions in terms of sleep patterns.…”
Section: Discussionmentioning
confidence: 99%
“…21 Os estudos constataram uma relação bidirecional entre a morbidade psicológica, a saúde mental e a qualidade do sono. O efeito indireto da sonolência diurna excessiva sobre a qualidade do sono não foi mediado pela morbidade psicológica.…”
Section: Discussionunclassified